Relevancia ontológica de la formación humanística en el desarrollo profesional de los estudiantes de Comunicación Social de la Universidad de Pamplona, sede de Villa del Rosario (2015)
This qualitative research shows the ontological relevance of the humanistic component in the professional development of Social Communication students at the University of Pamplona, based in Villa del Rosario. We identified the perception of humanistic training that energizes teaching practices and learning processes; the research showed that students and teachers are linking this component to educative community interaction, more from the practical sites of the Program than from their own classes of humanities. Subsequently, we analyzed the humanistic capacities that currently need to orientate the professional development and we found out that there is sensitivity to the context, appropriation of the anthropologic elements that are transmitted by the teacher and, consequently, coherence in the pedagogical performance and social requirement. Finally, the research proposes conceptual tools to strengthen humanistic principles in professional training and development of the students, starting from input and output categories. The input category refers to the anthropological components and the output category reveals the necessity of retaking a pedagogy that transcends utilitarism and prepares not only for professional work, but also for ethics and anthropology in order to give answer to the necessity of adopting a sustainable development model.